The Acoustic Vowel Space Of Anyi In Light Of The Cardinal Vowel System And The Dispersion Focalization Theory - Koffi, Ettien (My University, 2018)
The Cardinal Vowel System (CVS) and the Dispersion Focalization Theory (DFT) make an important assumption about the inventory of vowels in world languages. The claim is that languages organize their vowels in a certain way in the auditory-perceptual space so as to maximize intelligibility. The vowel diagrams of African languages in influential publications such as Welmers (1973: 20–45) explicitly or implicitly reflect this assumption. However, persistent confusions between [ɪ] and [e] among Anyi Morofu speakers have aroused my curiosity and led me to investigate the matter acoustically. The findings reported here show that the vowel space of Anyi Morofu is in a between and betwixt state. The data indicates that this dialect is moving from a nine-vowel system to an eight-vowel system through the merger of [ɪ] and [e]. There are also signs of the impending merger of [ʊ] and [o].
Keywords: Cardinal Vowel System; Dispersion Focalization Theory; Anyi; HUMANITIES and RELIGION::Languages and linguistics::Other languages::African languages